Development of audiobook learning media entitled "The Miracle of Hallwachs" to improve novel listening skills of grade XI vocational school students - Purwahida, Rahmah; Wulandari, Yosi; Nabilah, Norma; Yanez, Maria Angelica (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The use of audio-based learning media, such as the "Hallwachs Miracle" audiobook, has great potential in improving students' listening skills. This research aims to (1) develop the audiobook learning media "The Miracle of Hallwachs" and (2) test the validity and effectiveness of this audiobook media to improve the listening skills of grade XI students of SMK. This research uses a research and development (R&D) approach with the ADDIE model, namely (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. The subjects of this study include grade XI students of SMK Negeri 35 Jakarta, SMK Negeri 53 Jakarta and SMK PGRI 24 Jakarta. The data collection method in the study uses questionnaires used to analyze student needs, product validity tests by experts, and product effectiveness tests. The analysis technique used in this study is quantitative descriptive. The results of the study show that the learning media developed is valid and effective, which is evidenced by a percentage of 95.12% with a very feasible category from media experts. The results of the validity test from material experts showed a percentage of 96.28% with a very feasible category. The results of the validity test from linguists showed a percentage of 87.4% with a very feasible category. The results of the effectiveness test conducted in a small group showed that the percentage of effectiveness was 92.6% with the very feasible category, and the large group trial was 94.9% with the very feasible category. This shows that the learning media developed has excellent effectiveness. The results of this study show that the development of the audiobook learning media "The Miracle of Hallwachs" has proven to be effective in improving the novel listening skills of Class XI vocational school students.